Agricultural Credit: A Powerful Tool for Rural Youth Self-Employment - Lamichhane, Basu Dev (Journal of Development Review, 2021)
The assurance of agricultural credit, the government of Nepal should have investment in agricultural infrastructure; establish mechanism for agro eco-system, effective management of agro in-put, reliable insurance policy for agriculture, favorable policy for agriculture development, assurance of repayment of agricultural loan. The purpose of the paper is to highlight the prospects of agricultural finance to rural youth for self-employment. This study has used descriptive research design. Agricultural development programs and employment creation should be rural oriented and particularly targeted to the migrant people returning from abroad during the pandemic. Agriculture is sustained way for long -term employment to them. For the commercialization, modernization and development of agricultural sector various programs and activities has been implemented, but all of these are not accessed to targeted farmers. A specific financial institution for agricultural finance is needed and special package for youths is essential. The conclusion of the study shows that agricultural credit and rural youth employment have significant relationship with economic and social re-establishment of society. The findings of the study will benefit policy makers, economist, and bank and financial institutions (BFIs).